RELIGIOUS RECTITUDE: THE BEDROCK OF SOCIOPOLITICAL LAWS - Chakrabarty, Andrew Reginald (European Scientific Journal, ESJ, 2014)
Society is characterized by certain attributes that define its political and social conditions. ‘The State’ is essentially run by legal and political values that have more or less remained constant through the passage of time by virtue of the yardstick of ‘right’ and ‘wrong’. What this paper essentially does is to understand the philosophy of the entire jurisprudence and evolution of law which tells us what is right or wrong with respect to the absolutely unchanging philosophy that we have passed from generation to generation i.e. the teachings of any Religious Virtues /God. The analysis of this link throws great light on the evolution of our socio-political system. To understand the essence of the theory many parallels have been drawn, one important one being the ‘Social Contract Theory’ and its evolution from the theory of man’s natural submission to a higher power called God thus answering the question of great philosophical depth that is what is the philosophical origin of the ‘Social Contract Theory’? The idea itself, thus aims to understand the depths of how any socio-political system is ever infused with the ideals of God and in light of the given theories the paper thus concludes on the note that contrary to popular belief law and morality do not emerge due to the dynamic nature of society but are rather a strict set of guidelines that are misinterpreted narrowly which can be corrected when we trace back to the source of morality, which in my opinion, I believe we call, God.